Ambiguidades, deterioração e sentido da vida - doi: 10.4025/actascilangcult.v33i1.7150 - Adilson Barbosa (Acta Scientiarum. Language and Culture, 2011)
CONY, Carlos Heitor. A morte e a vida. Rio de Janeiro: MemVavMem, 2007, 157 p. ISBN: 9788576880530